Of "Sluts" and "Arseholes": Antagonistic Desire and the Production of Sexual Vigilance. (October 2017) - Fanghanel, Alexandra; Lim, Jason
This article examines a contemporary antagonism in gendered safety discourses—the imperative to be free in public space against the obligation to be safe and "properly" feminine. We argue that this produces (and is produced by) contemporary rape culture, which might be contested through recourse to an agonistic ethic. Using qualitative interview data, we examine how participants contest victim-blaming discourses, while limiting how far they will accept the female body's right to occupy public space. This article has significant implications for approaching social justice, in particular justice for women and their right to occupy public space.